XI Symposium on probability and stochastic processes: CIMAT, Mexico, November 18-22, 2013 - Mena, Ramsés H.; Pardo, Juan Carlos; Rivero, Víctor; Uribe Bravo, Gerónimo (Progress in Probability, 2015)
This volume features lecture notes and a collection of contributed articles from the XI Symposium on Probability and Stochastic Processes, held at CIMAT Mexico in September 2013. Since the symposium was part of the activities organized in Mexico to celebrate the International Year of Statistics, the program included topics from the interface between statistics and stochastic processes. The book starts with notes from the mini-course given by Louigi Addario-Berry with an accessible description of some features of the multiplicative coalescent and its connection with random graphs and minimum spanning trees. It includes a number of exercises and a section on unanswered questions. Further contributions provide the reader with a broad perspective on the state-of-the art of active areas of research. Contributions by: Louigi Addario-Berry Octavio Arizmendi Fabrice Baudoin Jochen Blath Loïc Chaumont J. Armando Domínguez-Molina Bjarki Eldon Shui Feng Tulio Gaxiola Adrián González Casanova Evgueni Gordienko Daniel Hernández-Hernández Noemi Kurt Jaime Martinez A. Murillo-Salas Jan Pedersen J.L. Pérez Mark Podolskij Alfonso Rocha-Arteaga J. Ruiz de Chavez Orimar Sauri Shuenn-Jyi Sheu Gerónimo Uribe Bravo Youzhou Zhou.